Effectiveness of Implantable DEfibrillators Alert Systems: comparison between audible and vibratory alert. Issue 3 (March 2019) - Palmisano, Pietro; Pisanò, Ennio C.L.; La Rosa, Concetto; Ammendola, Ernesto; Zaccaria, Maria; Milanese, Giovanni; Lauretti, Maurelio; Rillo, Mariano; Aloisio, Angelo; Rago, Anna; Nigro, Gerardo; Accogli, Michele
Abstract : Introduction: Implantable cardioverter-defibrillator (ICD) alarm systems are an important means of monitoring device functioning. The aim of this study was to compare the ability of patients with sense two types of device alert systems: an audible alert and a vibratory alarm. Methods: The ability to recognize the alarms was assessed in three alarm tests performed in a series of consecutive ICD patients enrolled during routine outpatient device follow-up. To avoid overestimating the rate of patients able to sense the alarm, the first test was performed without forewarning. Subsequently, the second test was performed after the patients had been forewarned. Finally, to assess the learning effect of a demonstration test, a third test was performed, again without forewarning. Results: A total of 528 patients (65.4 ± 14.4 years, 74.6% male) were enrolled: 347 (65.7%) with an audible alert-endowed device and 181 (34.3%) with a vibratory alarm-endowed device. When emitted without warning, the alarms were sensed by 72.4% of patients. When patients were forewarned, the probability of sensing the alarms rose to 92.5% ( P  < 0.001). In both cases, the vibratory alarm was more likely to be sensed than the audible alert (77.3 vs. 67.7% in the first case; 96.1 vs. 87.9% in the second case; all P  < 0.05). Conclusion: ICD alarms emitted in an outpatient setting are sensed by a large proportion of patients, but not by all. Training patients by means of demonstration tests significantly increases the rate of patients who recognize the alarm. Vibratory alarm seems to be more effective than audible alert.